The Research Question - Ramos Galarza, Carlos Alberto (2016)
The research question is the key aspect in an investigation. Its approach is a product of the idea of research, the deepening of the theory of the phenomenon of interest, the review of previous studies, interviews with experts, among others. In the quantitative approach the research question mentions the study of the objective reality, while in the qualitative approach it mentions the subjective reality. In this article a review is conducted of the process followed in the formulation of a research question and the required characteristics in the different research approaches. In conclusion, it is claimed that the question of qualitative research must possess the characterization of the construction of reality through meanings that emerge during the symbolic interaction of a human group. The question of quantitative research should make reference to the measurement, manipulation, and statistical analysis that may be performed on a certain phenomenon.